Wybór instrumentów dłużnych wykorzystywanych przez jednostki samorządu terytorialnego - obligacje vs kredyt - Kozuń-Cieślak, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Local government entities have been entitled to incur a debt on the capital market. The purpose of the paper is showing the attributes of the municipal bonds as a debt instrument. The study presents: - main factors that are most deciding on the choice of the debt instrument, - the comparative analysis of the capital cost for municipal bonds and bank credit in Poland (2000--2004), - the comparative analysis of issuing costs for public and private placement of municipal bonds. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 200-214